Draft Genome Sequence of Halomonas smyrnensis AAD6(T) - (:unkn) unknown (AMER SOC MICROBIOLOGY, 2012)
Halomonas smyrnensis AAD6(T) is a Gram-negative, aerobic, exopolysaccharide-producing, and moderately halophilic bacterium that produces levan, a fructose homopolymer with many potential uses in various industries. We report the draft genome sequence of H. smyrnensis AAD6(T), which will accelerate research on the rational design and optimization of microbial levan production.